HOG based object detection and classification - Venkateswara Rao, N; Anil Kumar, G; Harish, B (International Journal of Engineering and Technology, 2018)
The intension of the project is to classify objects in real world and to tracks them throughout their life spans. Object detection algorithms use feature extraction and learning algorithms to classification of an object category. Our algorithm uses a combination of â€œhistogram of oriented gradientâ€ (HOG) and â€œsupport vector machineâ€ (SVM) classifier to classify of objects. Results have shown this to be a robust method in both classifying the objects along with tracking them in real time world.Â Â